Towards resolving and redefining Amphipyrinae (Lepidoptera, Noctuoidea, Noctuidae): a massively polyphyletic taxon. (2nd March 2019) - Keegan, Kevin L.; Lafontaine, James Donald; Wahlberg, Niklas; Wagner, David L.
Abstract: Amphipyrinae have long been a catchall taxon for Noctuidae, with most members lacking discernible morphological synapomorphies that would allow their assignment to one of the many readily diagnosable noctuid subfamilies. Here data from seven gene regions (> 5500 bp) for more than 120 noctuid genera are used to infer a phylogeny for Amphipyrinae and related subfamilies. Sequence data for 57 amphipyrine genera – most represented by the type species of the genus – are examined. We present here the first large‐scale molecular phylogenetic study of Amphipyrinae and the largest molecular phylogeny of Noctuidae to date; several proposed nomenclatural changes for well‐supported results; and the identification of areas of noctuid phylogeny where greater taxon sampling and/or genomic‐scale data are needed. Adult and larval morphology, along with life‐history traits, for taxonomic groupings most relevant to the results are discussed. Amphipyrinae are significantly redefined; many former amphipyrines, excluded as a result of these analyses, are reassigned to other noctuid subfamily‐level taxa. Four genera, Chamaeclea Grote, Heminocloa Barnes & Benjamin, Hemioslaria Barnes & Benjamin and Thurberiphaga Dyar, are transferred to the tribe Chamaecleini Keegan & Wagnertribe n. in Acontiinae. Stiriina is elevated to Stiriinaerev. stat., Grotellina is elevated to Grotellinaerev. stat. and Annaphilina is elevated to Annaphilinirev. stat. Acopa Harvey is transferred to Bryophilinae, Aleptina Dyar is transferred to Condicinae, Leucocnemis Hampson and Oxycnemis gracillinea (Grote) are transferred to Oncocnemidinae, Nacopa Barnes & Benjamin is transferred to Noctuinae and Narthecophora Smith is transferred to Stiriinae. Azenia Grote (and its subtribe Azeniina), Cropia Walker, Metaponpneumata Möschler, Sexserrata Barnes & Benjamin and Tristyla Smith are transferred to Noctuidae incertae sedis. Hemigrotella Barnes & McDunnough (formerly in subtribe Grotellina) is retained in Amphipyrinae. Argentostiria Poole and Bistica Dyar are retained in Stiriini but removed from incertae sedis position. This published work has been registered on ZooBank:http://zoobank.org/urn:lsid:zoobank.org:pub:4A140782‐31BA‐445A‐B7BA‐6EAB98ED43FA . Abstract : Fifty‐seven genera from Amphipyrinae are sequenced and found to belong in ten separate subfamily‐level taxa, including one entity that might represent an unrecognized subfamily (for Cropia ). Stiriinae is elevated to full subfamily status, as is Grotellinae, and a new tribe (Chamaecleini) in Acontiinae is described. Metoponiinae is greatly re‐evaluated, with the implication that Cydosiinae, a showy group of noctuids, being embedded in Metoponiinae, will need to be pulled back to a tribe.